Field reports form for submitting seasonal observations of Iowa birds, Rita Goranson, fall 1992 - Goranson, Ritaet al (1992)
Fall report of birds found in and around Cerro Gordo County contributed by Rita Goranson. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1992. Plustek - flatbed